Neural Responses to Visual Food Cues According to Weight Status: A Systematic Review of Functional Magnetic Resonance Imaging Studies - Pursey, Kirrilly M.; Stanwell, Peter; Callister, Robert J.; Brain, Katherine; Collins, Clare E.; Burrows, Tracy L. (Frontiers in Nutrition, 2014)
Emerging evidence from recent neuroimaging studies suggests specific food related behaviours contribute to the development of obesity. The aim of this review was to report the neural responses to visual food cues, as assessed by functional magnetic resonance imaging (fMRI), in humans of differing weight status. Published studies to 2014 were retrieved and included if they: used visual food cues, studied humans >18 years old, reported weight status, and included fMRI outcomes. Sixty studies were identified that investigated the neural responses of healthy weight participants (n=26), healthy weight compared to obese participants (n=17), and weight loss interventions (n=12). High calorie food images were used in the majority of studies (n=36), however, image selection justification was only provided in 19 studies. Obese individuals had increased activation of reward-related brain areas including the insula and orbitofrontal cortex in response to visual food cues compared to healthy weight individuals, and this was particularly evident in response to energy dense cues. Additionally, obese individuals were more responsive to food images when satiated. Meta-analysis of changes in neural activation post- weight loss revealed small areas of convergence of activation across studies in brain areas related to emotion, memory and learning such as the cingulate gyrus, lentiform nucleus and precuneus. Differential activation patterns to visual food cues were observed between obese, healthy weight and weight loss populations. Future studies require standardisation of dietetic variables and fMRI outcomes to enable more direct comparisons between studies.